2009
DOI: 10.1152/japplphysiol.91501.2008
|View full text |Cite
|
Sign up to set email alerts
|

Interacting effects of genioglossus stimulation and mandibular advancement in sleep apnea

Abstract: Oliven A. Interacting effects of genioglossus stimulation and mandibular advancement in sleep apnea. J Appl Physiol 106: 1668-1673, 2009. First published February 19, 2009 doi:10.1152/japplphysiol.91501.2008 and stimulation of the genioglossus (GG) have been shown to improve upper airway patency, but neither one achieves the effect of continuous positive airway pressure (CPAP) treatment. In the present study we assessed the combined effect of MA and GG stimulation on the relaxed pharynx in patients with obstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 30 publications
1
27
1
1
Order By: Relevance
“…Similarly, Dieltjens et al 38 demonstrated the additional reduction in OSA severity patients experienced when sleeping in the lateral position was done in conjunction with wearing an oral appliance. Last, Oliven et al 39 assessed the effect of a combination of electrical stimulation of the genioglossus with mandibular advancement (targeting muscle responsiveness and anatomy/collapsibility respectively) on the Pcrit in 14 OSA patients under propofol-induced anesthesia. Although the authors did not assess the effect of these interventions on OSA severity, their findings indicate that there was an additive improvement in Pcrit compared with individual manipulations, with a number of patients in the combination group achieving a Pcrit ≤ 5 cmH2O, which should lead to a resolution of OSA.…”
Section: Does Combination Therapy Have a Future In Sleep Medicine?mentioning
confidence: 99%
“…Similarly, Dieltjens et al 38 demonstrated the additional reduction in OSA severity patients experienced when sleeping in the lateral position was done in conjunction with wearing an oral appliance. Last, Oliven et al 39 assessed the effect of a combination of electrical stimulation of the genioglossus with mandibular advancement (targeting muscle responsiveness and anatomy/collapsibility respectively) on the Pcrit in 14 OSA patients under propofol-induced anesthesia. Although the authors did not assess the effect of these interventions on OSA severity, their findings indicate that there was an additive improvement in Pcrit compared with individual manipulations, with a number of patients in the combination group achieving a Pcrit ≤ 5 cmH2O, which should lead to a resolution of OSA.…”
Section: Does Combination Therapy Have a Future In Sleep Medicine?mentioning
confidence: 99%
“…These increases have been attributed to decreases in pharyngeal collapsibility (14,16,17), which decreases the back pressure to inspiratory airflow (27). In previous studies, stimulating the genioglossus muscle and hypoglossal nerve led to an approximately 3-to 5-cm H 2 O decrease in critical pressure, which can account for an approximately 150-to 250-ml/s increase in maximal inspiratory airflow (18,19).…”
Section: Mechanism For Increased Airflow During Stimulationmentioning
confidence: 99%
“…In these prior studies, investigators scrutinized EEG and ECG signals to exclude responses associated with cortical or autonomic activation (13,18,19). Additional studies with implantable nerve cuff (13) and fine-wire electrodes have demonstrated responses to selective lingual muscle stimulation during sleep and anesthesia (13)(14)(15)(16)(17). The present study also screened for evidence of cortical and autonomic activation, and further required strict temporal synchrony between the stimulus burst and airflow response to exclude arousal responses from the analysis.…”
Section: Arousalsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not evaluate systematically the reproducibility of our results, but current and previous experience based on insertion of additional electrodes in the same area of stimulation suggests that the effects of stimulation are closely reproducible. Small changes in the level of anaesthesia, as well as head or mandibular position known to affect the response to GG contraction [33], could occur between the evaluations of the two sites of stimulation, despite our efforts to maintain stable conditions. However, the two sites were evaluated in random order to prevent systematic error.…”
Section: Sleep-related Disorders Y Dotan Et Almentioning
confidence: 99%